2003
DOI: 10.1002/app.11923
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerizations of carbon dioxide and epoxides in the presence of rare earth coordinate catalyst

Abstract: Carbon dioxide (CO 2 ) as a direct material was copolymerized with epoxides to synthesize new aliphatic polycarbonates, and the copolymerization was catalyzed by the coordinate catalyst composed of rare earth yttrium phosphonate and triisobutylaluminum [Y(P 204 ) 3 -A1(i-Bu) 3 ]. The epoxides used in this research included epichlorohydrin (ECH) and some new glycidol ether (GE) monomers prepared by the reaction of ECH and phenol or alcohol, such as ␣-allyl glycidol ether, ␤-chloroethyl glycidol ether, benzene g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…60 atm) for 44 h at 35 8C. Guo et al [13] also reported copolymer product of AGE-CO 2 using Y(P 204 ) 3 -Al(i-Bu) 3 catalyst under 30-40 atm CO 2 pressure for 24 h at 60 8C. Our previous work [14] also revealed the copolymerization of AGE and CO 2 using Co-Zn double metal cyanide catalyst at 9.6 atm for 36 h at 50 8C.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…60 atm) for 44 h at 35 8C. Guo et al [13] also reported copolymer product of AGE-CO 2 using Y(P 204 ) 3 -Al(i-Bu) 3 catalyst under 30-40 atm CO 2 pressure for 24 h at 60 8C. Our previous work [14] also revealed the copolymerization of AGE and CO 2 using Co-Zn double metal cyanide catalyst at 9.6 atm for 36 h at 50 8C.…”
Section: Resultsmentioning
confidence: 80%
“…It is interesting to note that previous works reported mainly the formation of polycarbonate in the reaction of AGE with carbon dioxide [12][13][14]. Lukaszczyk et al [12] used a mixed catalyst system based on ZnEt 2 and pyrogallol for the copolymerization of AGE with CO 2 at high CO 2 pressure (ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbonate or ether unit content in the copolymerization product was calculated from 1 H-NMR spectra according to literature [22]. 13 C-NMR can also be useful in that each of the carbonates, be it cyclic or polymer, gives a unique signal. IR spectra of the polymers were obtained with a React IR (ASI Model 1000).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work [12], we also reported the synthesis of PMEC using immobilized quaternary ammonium salt catalysts. The copolymerization of PGE and CO 2 was also studied using Y(P 204 ) 3 -Al(i-Bu) 3 catalyst [13].…”
Section: Introductionmentioning
confidence: 99%